Patriotic education in the Soviet military periodical press (1960-1990s) - Karekenov, М.; Shurentayev, А. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article elaborates on the scientific work of the Press on patriotic education of military personnel. The work of scientists who studied the issues raised by mass media dedicated to patriotic work with military personnel in the Union of Soviet Socialist Republics, including articles on patriotic education in print media, was analyzed. The leadership of the Soviet Union gave an important place to the mass media, including military periodicals. With their help, they purposefully influenced the minds of young people, instilled patriotic qualities in them. Military periodicals and mass media played a special role in the work of patriotic education of the Soviet army. Military journalism was used as one of the components of educational tools. At the same time, military printed pages are considered as a set of mass media as a means of informing the population about the novelty of military life. In those years, there was a high interest in the topic of patriotic education among scientists and practitioners. Many studies have been devoted to this problem. Various aspects of the education of patriotic Patriots have become the subject of research for several candidate and doctoral theses. However, it was noted that the researchers did not pay proper attention to the activities of military publications on patriotic education of military personnel in the 1960s and 1990s. During the Soviet period of the country’s development, there is a wide range of research on patriotic topics. The object of scientific attention of social historians of this period was «Soviet patriotism» as the basis for spiritual and political education of the military personnel. Today, the focus of work on the issues of patriotic education is also significantly changing. In the research work, there is a need to analyze the conflict of interests of patriotism in the individual and society